Nutritional status of eleven-year-old children in the Western Cape Province of South Africa - Steyn, Nelia P.(Nelia Patricia) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1986.